Sosialisasi Menumbuhkan Jiwa Entrepreneur melalui Kreativitas dan Inovasi pada Siswa - Vuspitasari, Benedhikta Kikky; Hapsari, Veneranda Rini; Usman, Usman; Silvester, Silvester (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Service to this community is to provide an overview of the importance of cultivating an entrepreneurial spirit from an early age through creativity and innovation. Methodology: Theoretical and practical approach methods, through lectures, this method used to convey the main theoretical concepts that must be understood and mastered by participants. Apart from that, the demonstration method, apart from lectures, this method can be used to improve training participants' understanding of the form of identifying statements or opening participants' thoughts in understanding how to foster participants' entrepreneurial spirit. Results: The results of the activities showed that all participants were enthusiastic and enthusiastic in participating in this activity where they show that creativity and innovation are within them so they can easily practice these activities. Conclusions: This activity was able to provide additional knowledge and new insights. It can be said that this activity successfully encouraged students' creativity and innovation in utilizing opportunities in their local environment. The participants were also very enthusiastic in following the activity, especially during the practical sessions. With this activity, students did not get bored of participating in learning activities because it was a combination of theory and direct practice, allowing them to apply it directly at home. Limitations: Activity Lack of practicum is a limitation in this activity. Contribution: This activity is able to achieve previously desired.